Less is More: Right Triangle Relationships (pp. 23--41) - Jacob, Lisa (Ohio Journal of School Mathematics, 2020)
As educators, we must decide which tools are the most strategic to use when designing and implementing classroom lessons. With numerous free dynamic softwares and pricy handheld tools availabe, it can become overwhelming to create and administer daily lessons to our students. After reflecting on a 2-day Special Right Triangle Lesson I fasciliatated, I learned that "less is more."